Identifying the strengths and weaknesses of conservation planning at different scales: the Coral Triangle as a case study - Cheok, Jessica; Weeks, Rebecca; Pressey, Robert L. (Ecology and society, 2019)
Each year, hundreds of conservation plans are developed to direct limited resources toward conservation in priority areas. Conservation plans are developed at different levels, defined here as points on a range of spatial extent varying from global to local. However, approaches to integrate plans effectively across levels remain elusive. To plan across multiple levels most effectively, the relative strengths and weaknesses of planning at different levels must be understood. Taking the Coral Triangle region of the western Pacific Ocean as a case study, we apply an adapted social-ecological system (SES) framework to assess the scalar coverage of conservation plans, i.e., the extent to which plans developed at one level adequately consider the social and ecological levels and components (i.e., resource units, resource systems, governance systems, actors) of an SES. No conservation plans we assessed had complete cross-level coverage. Plans most adequately addressed social and ecological components at the same level of planning and, to a lesser extent, lower levels. In line with previous literature suggesting that social factors are most relevant at local levels, we found that local-level plans engaged with the greatest number of stakeholder groups, whereas higher level plans more adequately addressed ecological components. Given that it appears more practicable for higher level plans to consider components at lower levels, the onus should fall on higher level planning to link to lower levels. Achieving complete cross-level coverage will require vertical interactions between planning processes at different levels, and conceiving of planning processes across all levels as connected planning systems. We demonstrate how an adapted SES framework can be used by conservation planners to assess the cross-level coverage of their own plans and to formulate appropriate conservation objectives to address social and ecological components at different levels.